Decyzja polityczna jako pozakonstytucyjny instrument ochrony państwa – wizja Carla Schmitta - Bogucki, Szymon (PRAWO i WIĘŹ, 2024)
Decisions play an important role in the process of state governance and management. Contemporary literature emphasizes the importance of administrative decisions, analyzes their nature and function, and places them against the background of the constitutional principles of a democratic constitutional state. Carl Schmitt’s writings contain original reflections on political decisions, to which the author assigns a legal value. He regards them as sources of law superior to norms. He thus modifies the theory of decisionism. According to Schmitt, norms do not fulfill their function in states that have never existed before (exceptional, unique states). Through an analysis of Carl Schmitt’s texts, the author attempts to reconstruct the idea of the political decision as an extraordinarily coordinated instrument responsible for the protection of the state and the constitution.